(untitled) (Journal of Bangladesh Academy of Sciences, 2015)
Any deposition techniques lead to the production of rough surfaces. Some researchers proposed a pair of coupled continuum equations, which models the molecular beam epitaxy. This model was used to generate a rough surface of Fe, which is deposited on a Ag substrate. Then use of recursion method of Haydock with the parameter of tight binding linearized muffin tin orbital method of Anderson revealed that the t2g and eg bands are nondegenerate at bulk and [100] plane but near the rough surface, the degeneracy is broken and splitting of density of states depends on the curvature of the surface. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 37-43, 2015